White-faced monkey (Cebus capucinus) ecology and management in neotropical agricultural landscapes during the dry season - Williams, Heather E (2001)
Habitat use by a C. capucinus troop was studied in an agricultural landscape during late dry season (March-April 1994) in northwest Costa Rica. Riparian forests, palm canals and living fence rows accounted for 82 % of observations, significantly more than the other six habitats present. The study troop consumed 24 species of plants and five animals. Feeding concentrated on the introduced African oil palm (Elaeis guineensis) (33.6 %) and mango (Mangifera indica) (27.2 %), found mostly in palm canals and mango orchards respectively. The troop rested between 0930-1330 hr and fed and moved between 0530-0930 hr and 1330-1730 hr. Living fence rows were used as travel routes or corridors and less intensively for other activities.